THE IMPACT OF DEVICE, DEMOGRAPHICS AND ACTIVITIES ON THE ATTITUDE WHILE ASSESSING SOCIAL MEDIA: AN EMPIRICAL EVIDENCE FROM THE UNIVERSITIES IN MALAYSIA - Hamid, Junainah Abd; Shukri, Shakeerah Mohd; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of existing study is to examine the impact of device, demographic and activities on the attitude of the student while assessing the social media. Data were gathered from the universities that are situated in Shah Alam Malaysia and SPSS was employed to test the hypothesis. The results show that positive nexus among the device, demographic and activities on the attitude of the student while assessing the social media.